2018
DOI: 10.1111/hiv.12663
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of high‐resolution anoscopy for anal cancer screening in HIV‐infected patients

Abstract: HRA was generally well tolerated and may be an acceptable screening approach for patients at high risk of anal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 32 publications
3
19
0
Order By: Relevance
“…8,9 ACSC survey respondents rated the potential benefit of clinic attendance to their health very positively, similar to previous studies showing high patient satisfaction with anal dysplasia screening and evaluation. 10 No-show rates in the ACSC were comparatively low for an inner-city clinic, supporting patient acceptance of the service. The majority of survey respondents reported learning about anal dysplasia and AC in their physician’s office and had fair knowledge of risk factors, but an analysis of the referral patterns to the ACSC from individual HIV providers suggested that not all consistently perform AC screening; this observation is also supported by the low proportion of survey respondents reporting prior DARE and anal cytology screening.…”
Section: Discussionmentioning
confidence: 89%
“…8,9 ACSC survey respondents rated the potential benefit of clinic attendance to their health very positively, similar to previous studies showing high patient satisfaction with anal dysplasia screening and evaluation. 10 No-show rates in the ACSC were comparatively low for an inner-city clinic, supporting patient acceptance of the service. The majority of survey respondents reported learning about anal dysplasia and AC in their physician’s office and had fair knowledge of risk factors, but an analysis of the referral patterns to the ACSC from individual HIV providers suggested that not all consistently perform AC screening; this observation is also supported by the low proportion of survey respondents reporting prior DARE and anal cytology screening.…”
Section: Discussionmentioning
confidence: 89%
“…While anal cancer screening has recently been shown to be acceptable to persons living with HIV, 26 , 41 multiple barriers to accessing such care have been documented. 28 , 42 , 43 These barriers may also be more significant among lesbian, gay, bisexual, transgender, and queer (LGBTQ) persons.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 The acceptability questionnaire indicated that 62.5% of the participants did not feel discomfort during the exam, which corroborates data found in the literature describing high tolerability between MSM and men living with HIV/AIDS, especially at the time of performing HRA. [27][28][29] All participants reported that they would undergo the proctological examination again if necessary. One study obtained similar results: 100% of patients who completed their survey stated that they would return for a follow-up HRA if recommended.…”
Section: Discussionmentioning
confidence: 99%
“…One study obtained similar results: 100% of patients who completed their survey stated that they would return for a follow-up HRA if recommended. 27 These factors are important considerations for the caregivers of these patients, particularly during preprocedure counseling. [27][28][29][30] According to the present data, HIV transmission occurred mainly through sexual intercourse, and 40.7% had more than ten years of infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation